Skin Signs of Systemic Disease TBL - Roxana Chapman; Richard Sabina; David Thomas (Association of American Medical Colleges, 2015)
Abstract Introduction Teaching dermatology to medical students and interns poses unique challenges but provides an excellent learning experience because many skin diseases look similar to the untrained eye. Years of practice are generally needed before a new practitioner learns to integrate memorized facts with history and physical findings. This resource was designed to enable learners to recognize common skin signs of disease, such as hair loss, and how it may be the initial manifestation of an autoimmune connective tissue disorder. Methods This team-based learning (TBL) module on skin disease is directed at second-year medical students and enables learning in an integrative, adaptive and reflective manner. First, students were assigned reading on neutrophilic dermatitis, urticaria, lupus, and scleroderma, and then given a five-question quiz designed to assess individual, as well as team knowledge of the reading and course objectives. This is then followed by application questions presented in the form of case vignettes that require the student teams to use provided history and clinical photos to piece together a narrative that cover all of the data. Results We have successfully run this TBL for the past 3 years in our M2 Winter semester musculoskeletal organ system course. Discussion This TBL module relies on application of knowledge gained from written material and applied to a changing clinical picture designed to simulate clinical practice. It requires drawing knowledge from multiple sources (lectures, online reading, and basic science) and applying it to develop a logical diagnosis and treatment strategy. In the upcoming age of telemedicine, these will be important practitioner skills, as they will need to be able to ask pertinent questions and develop a diagnostic and treatment ladder based on photographs and history.